THE IMPACT OF CURRENCY AUCTION ON THE VARIABILITY OF THE EXCHANGE RATE IN IRAQ 2004-2015 - محمود داغر محمود محمد; محمد بلال قاسم (Journal of Economics and Administrative Sciences, 2017)
The transition states that Iraq economy lived it after 2003, and the change in tools used by monetary policy based on C.B.I law 56 in 2004, under the especially situation for the economy (structural imbalances and the weakness of banking & financial sector). The monetary policy adopted the inflation targeting policy to mantain the monetary stability in the economy and considered it an incubator for future growth. It used the exchange rate as a nominal anchor to achieve the goal (because the rentier of economy, finance Shallowness & separation between real sector and finance sector, all this cause the normal channel to transfer the effect of monetary policy (interest rate) ineffective. For all that the monetary policy used the Auction as a mechanism to effect on exchange rate. And it’s succeed on controls the exchange rate and reduce the gap between the official price and market price to keep the exchange rate relatively stable for period 2004-2015 down to the stability of prices & purchasing power. But succeed of Auction caused pressure on international Reserves in the C.B.I, under the big government expenditure (especially the consumption expenditure) compared to a decrease of oil return, which represent the only source to supply the foreign currency. That makes exchange rate in the future inactive to keep the stability in the price and decrease the inflation. But the Auction still the only active tool used by the monetary policy under the especially situation the Iraqi economies lived.